Immersive competence and immersive literacy: Exploring how users learn about immersive experiences - Steed, Anthony; Archer, Dan; Izzouzi, Lisa; Numan, Nels; Shapiro, Kalila; Swapp, David; Lammiman, Dinah; Lindeman, Robert W. (Frontiers in Virtual Reality, 2023)
While immersive experiences are still a relatively immature medium, there are millions of consumer devices in use. The level of awareness of the forms of the interface and media will vary enormously across the potential audience. Users might own personal devices or might encounter immersive systems in various venues. We introduce the term immersive competence to refer to the general practical knowledge and skills that users accumulate about how typical immersive interfaces work -- the ways in which buttons are used, main locomotion techniques, etc. We then introduce the term immersive literacy to refer to awareness of how immersive interfaces are unique, when they might be appropriate, typical forms of media, etc. We sketch out how users develop competence and literacy with immersive media, and then highlight various open questions that are raised.